(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
In the Pharmaceutical process of different forms of medicines raw material & its quality plays an important role. During ancient time Vaidyas were themselves used to collect the raw materials herbs based on their occurrence and organoleptic characters, i.e., typical taste, texture, smell, color, and there types after selection they utilized them in preparing medicines. Based on their own observations, principles of drug processing and ideal quality of finished product, etc., have been documented by them. The principles were developed based upon the scientific parameters prevailing in those days. Materials and Method: Raw Shilajatu was subjected to Shodhana and Shodhita shilajatu was subjected to analytical study. The required materials for the process were collected from the Pharmacy of BLDEA’s AVS Ayurveda Mahavidyalaya pharmacy Vijayapur, analytical lab. Raw drugs were purchased from Dorle and Sons retailer from Kolhapur Maharashtra. Shilajatu shodhana was carried out according to reference mentioned in Rasaratna samuchaya. Analytical tests concern Indian Pharmacopeia methods were followed. Result: Raw Shilajatu took 5 ½ hour to 6hour in Shodhan procedure in both batches. Three days for drying. In analytical tests physical constants like pH ash value, solubility, specific gravity, moisture content etc result values were under normal limit.